Research Trends on Intellectual Capital and Competitive Advantage - Judijanto, Loso; Sono, Mohammad Gifari; Khadidjah, ST. Ramelan; Suyono, Windy Permata (West Science Journal Economic and Entrepreneurship, 2025)
This study provides a comprehensive bibliometric analysis of intellectual capital research, exploring its evolution, key themes, and global collaboration patterns. Using Scopus as the primary data source and VOSviewer for visualization, the study identifies major research clusters, influential authors, and emerging trends in intellectual capital and competitive advantage. The findings highlight a shift from knowledge management and information systems toward sustainability, corporate governance, and financial performance. The study also underscores the increasing role of digital transformation in intellectual capital research, emphasizing the integration of intangible assets with technological advancements. Additionally, the analysis reveals significant regional collaborations, with Spain, the United States, the United Kingdom, and emerging Asian economies playing dominant roles. The study contributes to the literature by offering insights into the theoretical and practical implications of intellectual capital management and its strategic impact on long-term business success.